Outcome of Patch Test on Crack Sole among Bangladeshi Population (Journal of Current and Advance Medical Research, 2020)
Background: Crack sole may produce significant morbidity among the physical labourer.Objective: The purpose of this study was to find out the patch test result in crack sole which was due to allergic contactants.Methodology: This test was conducted in the Department at Dermatology and Venereology of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh from July 2001 to June 2002 for a period of one year. Patients with crack sole were selected as study population. All patients were asked about the details clinical history. Patch test was done by individually prepared alminium Finn Chamber mounted on scanpore tape.Result: A total number of 15 patients were recruited for this study after fulfilling the inclusion and exclusion criteria. The age range was 8 years to 70 years. Among 15 patients 3 patients were patch test positive remaining 12 patients were patch test negative. Two patient were female and one was male. Conclusion: In conclusion patch test is positive among the crack sole patients.Journal of Current and Advance Medical Research 2020;7(2): 64-67